2019
DOI: 10.1002/jclp.22883
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cognitive behavioral therapy for insomnia comorbid to Parkinson's disease: A focus on psychological and daytime functioning with a single‐case design with multiple baselines

Abstract: Objective To test the efficacy of cognitive behavioral therapy for insomnia (CBT‐i) in Parkinson's Disease (PD) and to evaluate its impact on indices of daytime and psychological functioning. Method Fifteen patients with insomnia disorder (ID) comorbid to PD were enrolled in a single‐case design with multiple baselines. Total wake time, sleep efficiency, and daytime sleepiness were recorded on a sleep diary. Self‐reported measures of insomnia, anxiety and depressive symptoms, health‐related quality of life, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 81 publications
2
13
0
Order By: Relevance
“…This was consistent with the findings from a number of case studies (Macht, Pasqualini, & Taba, 2007; Mohlman et al, 2010; Richardson & Marshall, 2012; Veazey, Cook, Stanley, Lai, & Kunik, 2009) except for one (Feeney, Egan, & Gasson, 2005), which did not observe any significant improvements for anxiety. Similar positive findings were also reported by two studies adopting a multiple baseline single‐subject experimental design (SSED; Lebrun, Gély‐Nargeot, Rossignol, Geny, & Bayard, 2019; Reynolds, Saint‐Hilaire, Thomas, Barlow, & Cronin‐Golomb, 2019), which found significant reductions in anxiety at post‐treatment maintained at 6‐week and 3‐month follow‐ups.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This was consistent with the findings from a number of case studies (Macht, Pasqualini, & Taba, 2007; Mohlman et al, 2010; Richardson & Marshall, 2012; Veazey, Cook, Stanley, Lai, & Kunik, 2009) except for one (Feeney, Egan, & Gasson, 2005), which did not observe any significant improvements for anxiety. Similar positive findings were also reported by two studies adopting a multiple baseline single‐subject experimental design (SSED; Lebrun, Gély‐Nargeot, Rossignol, Geny, & Bayard, 2019; Reynolds, Saint‐Hilaire, Thomas, Barlow, & Cronin‐Golomb, 2019), which found significant reductions in anxiety at post‐treatment maintained at 6‐week and 3‐month follow‐ups.…”
Section: Resultssupporting
confidence: 83%
“…However, these were both limited by small participant numbers and relatively high attrition rates. Positive results for depression were also observed by two quasi‐experiments comparing CBT against psychoeducation (Berardelli et al, 2018) and no treatment (Tiihonen, Lankinen, & Viemerö, 2012), as well as two multiple baseline SSEDs adopting CBT for insomnia (Lebrun et al, 2019; Reynolds et al, 2019). One of the quasi‐experiments also reported significant improvements in apathy (Berardelli et al, 2018).…”
Section: Resultsmentioning
confidence: 86%
“…We could argue that this is possibly the result of non‐adequate therapeutic relationship between psychologist and patients, which led to patients more easily quit treatment. CBT for insomnia in individual modality in person in Parkinson's disease can induce positive changes in total wake time during the night, sleep efficiency, daytime sleepiness, quality of life, and psychological functioning (Leburn, Gely‐Nargeot, Rossignol, Geny, & Bayard, 2019). Rios Romenets et al (2013) combined CBT with light therapy.…”
Section: Cbt For Sleeping Disturbancesmentioning
confidence: 99%
“…It has reported CBT is beneficial to insomnia in patients with or without PD [31]. This may be because insomnia has been associated more with persistent psychological factors than specific disease characteristics in the general population [32], while the goal of CBT in treating insomnia is to alter erroneous perceptions, cognitive arousal and maladaptive behaviors toward sleep hygiene [33]. Another result revealed that sleep quality did not ameliorate, which demonstrates that CBT can influence sleep duration rather than sleep architecture.…”
Section: Discussionmentioning
confidence: 99%